Study of Modernization of Distillation Units and Applications of Nonlinear ROI Equity Model: A Case of Gayo Lues Patchouli Value Chain - Juanda Juanda; Lilik Sutiarso; Moch Maksum; Dyah Ismoyowati (Aceh International Journal of Science and Technology)
The inequity of benefits among actors in the Indonesian patchouli value chain has been taking place for decades. This phenomenon has made distillers unable to guarantee the patchouli oil quality, one of the essential things in the global market. The objective of this study was to evaluate effects of modernization of distillation units and applications of a nonlinear return on investment (ROI) equity model to the financial performance of actors in the value chain to help the government together with the actors making the correct decisions and policies in the development of patchouli oil business. The study was done in the Gayo Lues District, Aceh, Indonesia. The findings indicate that the distillers get the least benefits (the lowest ROI) among actors in the Gayo Lues value chain. Moreover, modernization of the distillation units can increase the ROIs of the actors in the value chain. But, to observe how to establish equity among the actors, a nonlinear ROI equity model was developed. To make ROIs of the actors equal, outputs of the model recommend that the ideal patchouli oil share ratio between farmers and distillers is around 3.3 – 3.4: 1. Outputs of the model also suggest that both net gross and profits per kg of medium middlemen should be increased, while both net and gross profits per kg of large middlemen should be decreased.